ANALISIS FAKTOR â FAKTOR YANG MEMPENGARUHI VOLUME EKSPOR DAN PRODUKSI KAKAO DI INDONESIA The Influence of Export Volume and Cocoa Production Width in Indonesi - Ananda, Restu; Iskandar, Sutarmo; Afriyatna, Sisvaberti (Muhammadiyah University of Palembang, 2017)
ABSTRACTÂ The objectives of this study were to find out the influence of, export tax, U.S dollar exchange rate and cocoa price export toward the volume of cocoa export, to know the influence of the domestic labor wage and the land width the production cocoa width and to know the trend of cocoa export price in Indonesia. This study has been conducted in Central Bureau of Statistics of South Sumatera Province and related institution. The time for collecting the data starting from April â June 2017.This study used secondary data method, the method for collecting the data was time series secondary method. The technique for analyzing the data to know the factors that influence the export volume and production cocoa width was multiple regression. To analyze the trend of chocolate export price for the next ten years, this study used simple linear analysis.The findings showed that the variable of export tax, U.S dollar exchange and export cocoa price were significantly influential eachother toward the cocoa export volume, partially the the export tax and U.S dollar exchange had significant effect while the export cocoa price had non-significant effect. Therefore, the domestic labor wage and the land width all influential significantly toward the production cocoa width, partially the domestic labor wage was influenced significantly toward the production cocoa width while the land was influenced insignificantly toward the production cocoa width. The findings also showed that the cost of cocoa export in 2016-2025 would be predicted to always increase.